2008
DOI: 10.1300/j135v07n04_04
|View full text |Cite
|
Sign up to set email alerts
|

Empathy Deficits in Siblings of Severely Scapegoated Children

Abstract: Empathy is a crucial concept in understanding not only child maltreatment, but its intergenerational transmission. One form of maltreatment, often involving both physical and emotional abuse, targets one child in the family, referred to as the "scapegoat." Historically, the scapegoat has been regarded as the only abuse victim; clinical experience demonstrates otherwise. In many families, siblings identify with the parent, joining in blaming the victim for the caretaker's abuse of that child. They demonstrate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Davies (2015) is one of the few to have explicitly considered sibling relationships that are not biological, recommending that professionals considering care arrangements should not only consider biological relationships. While most of the articles included in this review either do not specify the type of sibling relationship, or imply a focus on full biological sibling relationships, a small number of articles have given consideration to others like half-siblings and stepsiblings (Gatins, Kinlaw & Dunlap, 2014; Hollingsworth, Glass & Heisler, 2008). Hollingsworth, Glass & Heisler (2008) report that stepsiblings are particularly vulnerable to emotional abuse from parents who may draw siblings in to also cause harm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Davies (2015) is one of the few to have explicitly considered sibling relationships that are not biological, recommending that professionals considering care arrangements should not only consider biological relationships. While most of the articles included in this review either do not specify the type of sibling relationship, or imply a focus on full biological sibling relationships, a small number of articles have given consideration to others like half-siblings and stepsiblings (Gatins, Kinlaw & Dunlap, 2014; Hollingsworth, Glass & Heisler, 2008). Hollingsworth, Glass & Heisler (2008) report that stepsiblings are particularly vulnerable to emotional abuse from parents who may draw siblings in to also cause harm.…”
Section: Resultsmentioning
confidence: 99%
“…While most of the articles included in this review either do not specify the type of sibling relationship, or imply a focus on full biological sibling relationships, a small number of articles have given consideration to others like half-siblings and stepsiblings (Gatins, Kinlaw & Dunlap, 2014; Hollingsworth, Glass & Heisler, 2008). Hollingsworth, Glass & Heisler (2008) report that stepsiblings are particularly vulnerable to emotional abuse from parents who may draw siblings in to also cause harm. Gatins, Kinlaw & Dunlap (2014) however found that children and young people affected by divorce appear to be better adjusted when they have half-siblings compared to those who only have full biological siblings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that 79 % of the primary abusers were not the child's first degree relative; they included such caregivers as boyfriends, girlfriends, aunts, uncles, grandparents, adoptive parents, and stepparents. Most child victims appeared to be scapegoated within their family; this is another recognized form of abuse associated with sibling empathy deficits (Hollingsworth et al 2007). …”
Section: Household Dynamicsmentioning
confidence: 99%
“…Diese Ergebnisse wurden auch in Deutschland von Libal und Deegner [11] im Hinblick auf körperliche Gewalt repliziert. In einigen Fällen kommt es sogar zu schwerster körperlicher und psychischer Gewalt unter Geschwistern [12][13][14].…”
Section: Introductionunclassified